Synthesizing the Academic Administrators’ Competencies: Developing of a Model - Homa Rahmani; Asadollah Khadivi (مدیریت بهره وری)
Abstract: One of the most fundamental problems of universities is the lack of a suitable model for choosing the most qualified individuals for management positions.Hence, the present study sought to design a competency model for university managers.The research is qualitative in method and synthetic in type, and is conducted through content analysis while following practical aim.The scope of the current research includes scientific and research articles published in domestic and foreign valid journals from 2013 to 2023 in the field of academic administration competency.The statistical sample of the study was selected using a purposive method, which included 31 items were selected from among 80 articles. After multi-step refinement, data analysis and synthesis, the competency model of university managers with four overarching themes, eight organizing themes and 102 basic themes were drawn, with inclusive themes containing threshold competencies (personality and ethical), distinctive competencies (leadership and systematic thinking),core competencies (social, executive) and professional competencies (knowledge, skills). The results of this study offer important insights into the competencies required for university managers and can serve as a valuable resource for universities seeking to improve their selection process for management positions.   Key Words: research synthesis, competence, managers, higher education         1.Introduction The selection and appointment of competent managers is one of the most important and sensitive issue in the work process of any organization, which has received a lot of attention in recent years (Pour Faraj et al., 2023). Organizations need managers who can make correct decisions and provide creative solutions to problems and be accountable for their work and responsibilities (Vakilzadeh et al.,2023). Certainly, to become better managers, having a framework or a model to identify the required competencies will be a guide, and undoubtedly, having such qualifications is not only the distinguishing feature of the manager from other employees, but also provides the basis for the university's success in a scientific and dynamic environment. Hence, the current research tries to answer the following questions: What are the dimensions and components of academic managers' competencies? What is the competency model of academic managers? Literature Review Nowadays, if managers of organizations and universities want to achieve their goals, they should prioritize meritocracy and programs to improve their competencies. Research shows that competent management can influence the development and evolution of the university and implement the planned changes effectively (Shimoni, 2017). Management thinkers believe that developing the competence of managers is the key to the development of countries to such a degree that many successful countries in the world admit that if you train a manager, success in everything will follow (Davodi et al., 2021). Sheshpari and Momeni Mehmoui (2023) investigated the dimensions of managers' competence. They came to the point that the competence of managers is influenced by various factors such as their beliefs and values, personal, managerial and professional characteristics. The competency model of the American Association of Public Universities and Colleges (2016) consists of five competencies: managerial, interpersonal, personal, leadership and surplus characteristics. Szczepańska and Dacko (2014) also defined six criteria of scientific ability, analytical ability, personal characteristics, interpersonal skills, management skills and attitude for the university president. Erfani Khanghahi et al. (2021) have conducted a research entitled “presenting the competence model of managers of Islamic Azad University”. The findings of this research have classified the competence of Islamic Azad University administrators in seven dimensions of human communication competence, perceptual, managerial, professional, belief and value, individual and organizational. The current research experiences show that although each of the researches has a proper depth and precision in their work, there is no particular coherence between the researches. Additionally, the results are completely scattered, or the research done on the competence model of managers is not sufficient and comprehensive. Thus, it is concluded that one of the most significant perceived gaps is the lack of an integrated model for the competencies of university managers. Methodology The current research serves a functional purpose, employing a qualitative approach. It utilizes a research synthesis strategy through meta-synthesis, which is associated with inductive content analysis followed by a meta-synthesis of the analyzes conducted. What is considered in the current research is the use of thematic synthesis with the strategy of Sandelovski and Baros (2007). In exploring research related to the competencies of managers, the internal and external databases of Eric, Science Direct, Springer, Scopus, Al-Ziyur, Academic Jihad Scientific Information Database, Humanities and Cultural Studies Research Institute Portal, National Conference Publication Database, Noor and Samaneh Specialized Magazines Database Publications of the country, and keywords such as research synthesis, competence of managers, higher education, university and competence model have been utilized, covering the period from 1392 to 1402. The articles were thoroughly reviewed, and open coding was conducted using the line-by-line method. This process resulted in the identification of 102 codes that had a semantic connection. Basic themes were extracted and considered as codes, which were then classified into similar organizing themes according to the meaning. Finally, the the analysis yielded 102 basic themes, 8 organizing themes and 4 comprehensive themes. Triangulation method was used to ensure the validity of the findings. The technique of triangulation refers to the use of multiple sources of data to draw conclusions. Using multiple approaches in a study can lead to increasing the credibility of information. So, in order to increase the accuracy and reliability of the findings, the procedure proposed by King et al. (2018), the formula of the Holstein coefficient was also used. In this formula, M is the number of agreement in two stages of coding, n1 is the number of units coded in the first stage and n2 is the number of units coded in the second stage. The value of the Holstein index also fluctuates between zero and one. In this study, coding was done in two stages, in the first stage, 102 codes were identified and in the second stage, coding was done by another expert and 90 codes were extracted. The total number of agreeable codes in two stages was 174. Using the formula, the Holstein coefficient was calculated to be 0.91. Since this value exceeds 0.7, it indicates that the research findings possess good reliability. In the final step, using  the obtained thematic network, the conceptual model of university managers' competencies was drawn in the form of 4 comprehensive themes, 8 organizing themes and 102 basic themes. Result The most important competitive advantage of today's universities is their human capital. In other words, in the present era, the competitive advantage will be given to universities that have competent managers, and entrepreneurs who are intellectual and cultural, creative, risk-taking, position makers and opportunity creators in the competition market. Those who put talent and competency management in the priority of their work plans, and based on  the competencies, they attract and keep the most brilliant human talents so that they can maintain the territory of competition and create a competitive advantage in the competition scene. The findings of the research indicate that the developed model includes 4 comprehensive themes, 8 organizing themes and 102 basic themes. The overarching themes of this model are threshold competence, distinctive competence, core competence and professional competence. Research methodology provides a comprehensive and systematic view to managers' competencies for designing job analysis systems, human resource planning, selection, appointment, training, recruitment, evaluation and psychological and structural empowerment of university managers. It emphasizes that the managers of the country's universities should have personality, ethical, leadership, systematic thinking, social, executive, knowledge and skill competencies. Discussion The compiled model can be used as a strategic, analytical and operational management dashboard in policy making and decision making. In order to take advantage of the mentioned model, it is suggested that executive committees be formed in order to plan a competency-based system in the selection and appointment of university managers in the agenda of the Ministry of Science, Research and Technology. The innovation and the most important feature of this model is to pay attention to the combination of homogeneous, common and distinct concepts and cover all dimensions, components and indicators of competency models of previous researches.